Sequence and entropy-based control of complex coacervates. Issue 1 (December 2017) - Chang, Li-Wei; Lytle, Tyler; Radhakrishna, Mithun; Madinya, Jason; Vélez, Jon; Sing, Charles; Perry, Sarah
Abstract Biomacromolecules rely on the precise placement of monomers to encode information for structure, function, and physiology. Efforts to emulate this complexity via the synthetic control of chemical sequence in polymers are finding success; however, there is little understanding of how to translate monomer sequence to physical material properties. Here we establish design rules for implementing this sequence-control in materials known as complex coacervates. These materials are formed by the associative phase separation of oppositely charged polyelectrolytes into polyelectrolyte dense (coacervate) and polyelectrolyte dilute (supernatant) phases. We demonstrate that patterns of charges can profoundly affect the charge–charge associations that drive this process. Furthermore, we establish the physical origin of this pattern-dependent interaction: there is a nuanced combination of structural changes in the dense coacervate phase and a 1D confinement of counterions due to patterns along polymers in the supernatant phase. Monomer sequence is an emerging tool to precisely encode information (and thus structure and function) into polymer systems. Here the authors use sequence-control in complex coacervates to understand how monomer sequence translates to physical material properties.